Synthesis and structural characterization of new bioactive ligands and their Bi(III) derivatives. (11th October 2016) - Raheel, Ahmad; Imtiaz‐ud‐Din,; Andleeb, Sohaila; Ramadan, Simko; Tahir, Muhammad Nawaz
Abstract : Five new carboxylic acid precursors bearing thiourea group and their corresponding bismuth(III) complexes were synthesized and characterized using CHNS and inductively coupled plasma analyses and infrared and NMR ( 1 H, 13 C) spectroscopies. Single‐crystal X‐ray diffraction analysis was also carried out for one of the precursors. The behaviour of the compounds was bioassayed for antibacterial, antifungal, antioxidant and enzyme (lipoxygenase, α‐glycosidase and anti‐urease) inhibition activities. It is concluded that the interaction of the compounds with bismuth enhances both the antimicrobial and enzyme inhibition activities. The synthesized compounds may prove to be good therapeutic agents. Abstract : Five new pivaloylcarbamothioyl amino acids and their corresponding bismuth(III) derivatives were synthesized and characterized using sophisticated techniques. The behaviour of the compounds was bioassayed for antibacterial, antifungal, antioxidant and enzyme (lipoxygenase, α‐glycosidase and anti‐urease) inhibition activities.